Asuhan Kebidanan Pada Kehamilan Trimester III Di TPMB Rupi’ah Suparman - Teresya Aulaliah Dartanti; Fauziah Fitri Hernanto; Dewi Purwantiningsih (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
The aim of the research is to provide midwifery care to pregnant women in the third trimester using a midwifery management approach. Data collection instrument method is a tool used to collect research data. The instruments used are in accordance with pregnancy care, namely using a mother's card, MCH book, scales, tensimeter, metelin, LILA tape, fundoscope or Doppler, Poedji Rochjati score card, instruments for simple laboratory examinations in the form of Hb, urine protein and urine reduction. Physiological pregnancy results, if calculated from the time of fertilization to the birth of the baby, a normal pregnancy will take place within 40 weeks or 9 months according to the international calendar. Pregnancy is divided into three trimesters, where the first trimester lasts 0-12 weeks, the second trimester 13-24 weeks, and the third trimester 25-41 weeks. Midwifery care in pregnancy given to Mrs "I" aged 28 years GIP0A0 has been carried out in accordance with Minimum 10 T Standard Care service program policies include weighing and measuring height, measuring blood pressure, measuring LILA, measuring uterine fundal height, TT immunization, administering iron tablets, determining fetal presentation and fetal heart rate, interviewing, laboratory tests, and management.